Frontalis suspension using autogenous fascia lata – evaluation of long-term outcome - Dębski, Tomasz; Jethon, Józef; Pietruski, Piotr; Radzikowska, Elżbieta (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: To evaluate long-term outcome of frontalis suspension using autogenous fascia lata (frontalis suspension – FS) which is indicated in the treatment of severe blepharoptosis with minimal levator function. Material and methods: Fourty one patients (23 females, 18 males, aged 6–79 years, mean 41.4 years) who underwent FS between 1999 and 2009 were evaluated. Mean follow-up was 55 months. Functional outcome was measured on digital photographs by analysis of an upper eyelid margin position below the superior limbus. Following criteria were used: very good ( 5 mm). Aesthetic outcome was assessed in terms of lid contour, symmetry of lid height and lid crease. Patient satisfaction and life quality improvement were evaluated in the survey. Results: Functional outcome was very good in 36%, good in 59.3%, unsatisfactory in 4.7%. Recurrence occured in 4,6% and complications in 10,9% (lagophthalmos – 6.2%, entropion – 4.7%). Very good aesthetic outcome regarding lid contour, symmetry of lid height and lid crease was achieved in 76.6%, 53.6% and 51.6%, respectively. Patient satisfaction and life quality improvement was also very high. There were only 1.6% unsatisfied patients. Conclusions: FS is an efficient method in treatment of severe blepharoptosis.